Galaxy And Mass Assembly (GAMA): the wavelength dependence of galaxy structure versus redshift and luminosity - Kennedy, Rebecca; Bamford, Steven P.; Baldry, Ivan; Häußler, Boris; Holwerda, Benne W.; Hopkins, Andrew M.; Kelvin, Lee S.; Lange, Rebecca; Moffett, Amanda J.; Popescu, Cristina C.; Taylor, Edward N.; Tuffs, Richard J.; et al. (Oxford University Press, 2015)
We study how the sizes and radial profiles of galaxies vary with wavelength, by fitting Sersic functions simultaneously to imaging in nine optical and near-infrared bands. To quantify the wavelength dependence of effective radius we use the ratio, R, of measurements in two rest-frame bands. The dependence of Sersic index on wavelength, N, is computed correspondingly. Vulcani et al. have demonstrated that different galaxy populations present sharply contrasting behaviour in terms of R and N. Here we study the luminosity dependence of this result. We find that at higher luminosities, early-type galaxies display a more substantial decrease in effective radius with wavelength, whereas late types present a more pronounced increase in Sersic index. The structural contrast between types thus increases with luminosity. By considering samples at different redshifts, we demonstrate that lower data quality reduces the apparent difference between the main galaxy populations. However, our conclusions remain robust to this effect. We show that accounting for different redshift and luminosity selections partly reconciles the size variation measured by Vulcani et al. with the weaker trends found by other recent studies. Dividing galaxies by visual morphology confirms the behaviour inferred using morphological proxies, although the sample size is greatly reduced. Finally, we demonstrate that varying dust opacity and disc inclination can account for features of the joint distribution of R and N for late-type galaxies. However, dust does not appear to explain the highest values of R and N. The bulge–disc nature of galaxies must also contribute to the wavelength dependence of their structure